The Tradition of Mappasikarawa in the Bugis-Makassar Community Marriage: A Study of Islamic Law Philosophy - Idrus, Achmad Musyahid; Nurdin, Roswati; Qayyum, Rahman; Halim, Patimah; Amir, Rahmah (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The Mappasikarawa tradition is a unique tradition carried out after the marriage ceremony by the Bugis Makassar community, this practice has become a polemic in society because it is considered only a tradition with no foundation in Islamic law. This study aims to discuss the Mappasikarawa tradition in the marriage of the Bugis Makassar community from the perspective of Islamic legal philosophy. This research is an empirical legal study using an Islamic legal philosophy approach. There are two ways used in collecting data, namely; in-depth interviews and literature studies. The research was conducted in five regions in South Sulawesi namely; Makassar, Maros, Pangkep, Gowa, and Wajo, while the informants interviewed were traditional leaders, religious leaders, academics, women's leaders and wedding couples. This study concludes that the Mappasikarawa tradition practiced by the Bugis-Makassar people has a historical basis that is rooted in Islamic law, especially a tradition of 'urf. The philosophical values contained in touching certain parts of the wife's body do not contain polytheism because touching the wife's body is always preceded by blessings on the prophet and accompanied by good prayers. Because of this, the Mappasikarawa tradition which originates from local Bugis-Makassar values can actually be said to be part of sunnah-hashanah and has relevance to Islamic law where both are manifestations of benefit for married couples.